Policies, Progress and Challenges in Addressing Antimicrobial Resistance - Hilde Juzeniene Torhild; Andreas Geisler; Agnete Olga Kirstin (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Antimicrobial Resistance (AMR) poses a critical challenge to global healthcare systems, including Norway, despite its relatively low antibiotic consumption rate. This study aims to evaluate antibiotic resistance rates, analyze government policies, and explore progress in the development of antibiotics and alternative therapies in Norway. A qualitative descriptive design with a case study approach was used, combining data from policy documents, research articles, and semi-structured interviews with 30 respondents, including microbiologists, healthcare professionals, and policymakers from Oslo, Bergen, and Tromsø. Findings reveal that although Norway’s antibiotic resistance rate is lower than other European countries, certain bacteria, such as MRSA, Enterococcus faecium, and ESBL-producing E. coli, remain problematic in hospitals. The Norwegian government’s strict management policies, including prescription restrictions and diagnostic mandates, have effectively reduced resistance. In addition, research on new antibiotics and alternative therapies, such as phage therapy and probiotics, shows promise but requires further exploration. Challenges such as high R&D costs, resource constraints, and the global spread of resistant bacteria hinder progress. This study highlights the need for international collaboration, innovative funding models, and expanded research into alternative therapies. Future studies should address hospital-specific resistance challenges and strategies to accelerate antibiotic development. Norway’s experience provides valuable insights for global AMR management and policy.